ANALISIS PENGETAHUAN KONTEN PEDAGOGIK GURU MATEMATIKA DAN PENGARUHNYA TERHADAP MOTIVASI BELAJAR SISWA (STUDI KASUS SMP PLUS YAKPI SUSUKAN) - Mualifah Alifah; Toheri Toheri; Darwan Darwan (EduMa: Mathematics education learning and teaching, 2019)
This study aims to determine the pedagogicalÂ  conten knowledge in the classroom VII SMP Plus YAKPI Susukan and the effect on student learning motivation. Pedagogical conten knowledge play a very important role in student learning motivation, especially in mathematics.This study used a mixed method and the sample cluster random sampling. Data collection was taken using tests, quwstionnaires, and interviews. The results of the deskriptive analysis for conten knowledge of mathematic teacher ware as 100%, The results of the deskriptive analysis for pedagogical knowledge of mathematic teacher ware as 43,91%. Researcher suggestions for teachers so that the learning runs effectiveely, the teacher is expected to pay attention to pedagogical knowledge and balance with the knowledge of mathematical content, not just conveying material in class but also must pay attention to mathods and techniques so that the learning process is more optimal.Keywords: Ability, Interest, Spirit,TeachingÂ  KowledgeÂ